2017
DOI: 10.1111/bjd.15376
|View full text |Cite
|
Sign up to set email alerts
|

Determining Effects of Superfine Sheep wool in INfantile Eczema (DESSINE): a randomized paediatric crossover study

Abstract: SummaryBackground Despite limited evidence, woollen clothing has traditionally been considered to be an irritant that should be avoided by individuals with atopic dermatitis (AD). Wool fibres come in a range of diameters, and have beneficial thermodynamic and moisture transport properties. Objectives This study examines the effects of superfine merino wool on symptoms in participants with mild-to-moderate AD. Methods The trial was a 12-week, randomized, assessor-blinded, crossover, prospective, cohort study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Coarse diameter fibres of any fabric may irritate, but irritation is neither a general nor a specific property of wool. In fact, recent studies suggest that superfine or ultrafine Merino wool with finer fibre diameters may benefit AD management (85). Known allergens associated with textile processing are minimally present in wool garments today given current industry practices and are unlikely to lead to allergic reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coarse diameter fibres of any fabric may irritate, but irritation is neither a general nor a specific property of wool. In fact, recent studies suggest that superfine or ultrafine Merino wool with finer fibre diameters may benefit AD management (85). Known allergens associated with textile processing are minimally present in wool garments today given current industry practices and are unlikely to lead to allergic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent Australian studies have demonstrated that the wearing of superfine Merino wool garments next to the skin may significantly reduce AD severity in children under 3 years with mild AD (85) and in persons aged between 6-81 years of age with mild-severe AD (86). In these studies, the superfine Merino wool fibre did not produce cutaneous irritation in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…258 Stress and conflicts in the family may trigger AD in young children. Flares are associated with contact to non-familiar pets, swimming in chlorinated pools and direct skin exposure to wool (except superfine merino wool 259 ) and nylon textiles. 260 Prevention and early recognition of atopic respiratory diseases and food allergies are important during childhood and adolescence.…”
Section: Specific Considerations For Childrenmentioning
confidence: 99%
“…Interestingly, a recent study of the use of silk clothing in individuals with moderate to severe atopic dermatitis showed no demonstrable benefit from wearing silk. 16 This study and those of Su et al 11 and Spelman et al 17 show that fine-diameter Merino wool clothing should be considered acceptable for people with eczema and seems to be therapeutic to patients with mild to moderate atopic dermatitis.…”
Section: Discussionmentioning
confidence: 55%
“…9,10 Properly sourced and manufactured Merino wool clothing may be well tolerated and may actually be beneficial as an adjunct to other treatments. Su et al 11 showed an improvement in SCORing Atopic Dermatitis scores in children wearing superfine Merino wool as compared with cotton clothing. Properties of wool fabrics including heat transmission and release of perspiration may increase skin comfort and reduce pruritus, compared with other fabrics.…”
mentioning
confidence: 99%